Factors Influencing the Valgus Cut Angle—during Total Knee Arthroplasty—in Indian Population - Marya, Sanjiv; Singh, Chandeep; Kacker, Shitij; Velayutham, Sarthy; Desai, Rahul (The Journal of Knee Surgery, 2020)
The number of total knee arthroplasties performed in India and the world is increasing exponentially. The valgus cut angle (VCA) of the distal femur decides the final alignment achieved in the coronal plane. Little data are available regarding the ideal value for an Indian population and there is little consensus whether to use a single value for all knees or to individualize the angle for each patient. The parameters that can influence the value of this angle have not been evaluated thoroughly.Standard long leg X-ray (orthoscanogram) was used to calculate the VCA in 302 lower limbs (160 patients). Only Indian patients were included in the study; knees with bowed femurs were excluded. VCA, femoral length, medial hip offset, neck shaft angle, and hip knee ankle angle were measured manually. Demographic data such as gender, height, and weight were extracted from hospital charts. The correlation of VCA with the various parameters was evaluated using Pearson's correlation and its significance assessed using the independent Student's ‘t’ test.The average VCA was 7.4 degrees (range: 4–11 degrees). Age, gender, height, hip knee ankle angle (alignment) and body mass index (BMI) had no influence on the VCA. The neck shaft angle (r = –0.520, p = < 0.0001) and hip medial offset (r = 0.223, p = < 0.0001) were the only two parameters significantly and independently influencing the value of VCA. There is a wide variation in the value of VCA in the Indian population. Choosing a fixed VCA will lead to significant number of knees aligned outside the ideal 0- to 3-degree hip knee ankle angle. The neck shaft angle and the medial hip offset are the only two factors that influence the VCA. The patients' height, preoperative deformity, gender, and BMI had no influence on the VCA.
Keywords: valgus cut angle; hip medial offset; femoral bowing; total knee arthroplasty; neck shaft angle; alignment